Economic Globalization: Challenges and Threats of the Russian National Security - Shevchenko, Olga Mikhailovna; Dyatlov, Alexandr Viktorovich; Kurmalieva, Zarema Khasambievna; Volkov, Yury Grigorievich; Popov, Alexandr Vasilyevich (International Journal of Economics and Financial Issues, 2016)
The article considers tendencies and consequences of economic globalization performed mainly in the interests of Western countries. The realities of the contemporary world are hardly optimistic. At the beginning of the third millennium economic globalization leads the global community to a new state defined by a number of constructive and destructive processes. According to the authors, economic globalization not so much integrates the world as strengthens deep economic inequality of regions and countries. “New third world” is represented by the countries and territories where economic and sociocultural structures are fundamentally disrupted. Peculiarities of the development of this “new world” characterize almost all countries of the post-Soviet space. Sharp aggravation of the global competitiveness for the resources, markets, strategic transport communications actualize the problem related to ensuring the economic security of Russia. The article analyzes the twofold impact of economic globalization on national states with the domination of negative consequences for their economies that is a threat for the national security of these societies. The analysis of consequences of the world globalization for the developing countries allows to fix a new form of extremism – economic extremism. The article determines that basic threats of the economic security of Russia may include considerable dependence on the import of technologies and many kinds of consumer goods, turning the country into exclusively the exporter of natural resources, weakening of its positions on the markets of the CIS countries. Keywords: Economic globalization, economic security, multinational corporations, economic inequality, economic sanctions JEL Classifications: F52, F63